Continuous glucose monitoring in a cohort of prepubertal children with Type 1 diabetes mellitus : a comparison of glycaemic outcomes to clinical and biochemical markers of diabetes control - McDonnell, Ciara M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Paediatrics, 2009)
In type 1 diabetes, monitoring of glycaemic status is considered a cornerstone of diabetes care and vital in the prevention of diabetes complications. Intermittent daily self monitoring of blood glucose levels provides a limited view of a patient's glycaemic control whereas continuous glucose monitoring provides an ambulatory record of glucose levels which more accurately reflects glycaemic control. Available data on continuous glucose monitoring in children is limited, difficult to replicate and restricted to basic comparative analysis. This project aimed to devise a novel algorithm that would comparatively analyse CGMS data expanding on previously published methods to include quantitation of inter- and intra-day glycaemic variation. The CGMS was repeated on four occasions to ascertain if education and repeated CGMS use improved glycaemic variation or HbA1c and reduced hypoglycaemia. Finally, short-term outcomes of glycaemia were evaluated to ascertain if twice daily insulin regimens or behaviour are directly impacted by glycaemia.
Keywords: Paediatrics, M.D.; M.D. Trinity College Dublin